(untitled) (Research, Society and Development, 2022)
Zoonoses are not a one-way dynamic of infection from animals to humans. Like other diseases, the possibility of animals becoming infected with SARS-CoV-2 through contact with humans has been demonstrated. The objective of this manuscript is to perform a narrative review, through the analysis of the current scientific literature, regarding the possibility of zoonosis and reverse zoonosis of SARS-CoV-2 under the One Health perspective and possible implications for the future evolution of the virus. Current research shows that the virus has the potential for reverse zoonosis, infecting mammals in several parts of the planet. Mustelids, hamsters, felines and old-world monkeys are the animals that have shown the greatest susceptibility to SARS-CoV-2. The reverse zoonosis of SARS-CoV-2 has favored the emergence of variants which mutations have shown themselves to be adapted to the various particular physiological characteristics of the affected animal species, with the ability to return to humans. SARS-CoV-2 is likely to be persistent among mammals after the pandemic wave that affected humanity. Mitigation processes for zoonosis and reverse zoonosis of SARS-CoV-2 from a One Health perspective require actions at three levels: human environment, relationships between humans and domestic or captive animals, and surveillance and control of circulating virus among free-living animals.